2013
DOI: 10.1080/17458080.2013.832421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sonication time on enhancement of effective thermal conductivity of nano TiO2–water, ethylene glycol, and paraffin oil nanofluids and models comparisons

Abstract: This paper presents experimental and theoretical determination of the effective thermal conductivity of various base fluids and nano TiO 2 composition. Ultrasonically assisted sol-gel method was used for synthesising anatase TiO 2 nanoparticles and dispersing them into base fluids using sonication for the synthesis of nanofluids. It is observed that thermal conductivity enhancement is significantly higher than that of base fluid. The thermal conductivity shows an increment with the addition of nanoparticles an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(35 citation statements)
references
References 24 publications
2
32
0
1
Order By: Relevance
“…Brownian motion caused the colloidal particles to be uniformly dispersed in the base fluids and TiO2 NPs could not be separated from the dispersion when silenced. This observation provides greater value than previous research, confirming that as much as 5.8% thermal conductivity enhancement is achieved with a 2% volume fraction of TiO2 NPs at 2 hours of sonication time (Sonawane et al, 2015). The increased thermal conductivity was influenced by NPs size, shape, and properties as well as the interaction between NPs and the base fluid surface, which caused cluster formation (Xie et al, 2003;Leong et al, 2006).…”
Section: Thermal Conductivity Of the Base Fluids And Tio2-water Nanofsupporting
confidence: 67%
See 2 more Smart Citations
“…Brownian motion caused the colloidal particles to be uniformly dispersed in the base fluids and TiO2 NPs could not be separated from the dispersion when silenced. This observation provides greater value than previous research, confirming that as much as 5.8% thermal conductivity enhancement is achieved with a 2% volume fraction of TiO2 NPs at 2 hours of sonication time (Sonawane et al, 2015). The increased thermal conductivity was influenced by NPs size, shape, and properties as well as the interaction between NPs and the base fluid surface, which caused cluster formation (Xie et al, 2003;Leong et al, 2006).…”
Section: Thermal Conductivity Of the Base Fluids And Tio2-water Nanofsupporting
confidence: 67%
“…Increasing the CMC of CTAB only decreased the pH, because the concentration of CTAB cationic surfactant caused an increase in positive charge thus the fluid is more acid. Sonawane et al (2015) investigated TiO2-water nanofluid with optimum sonication times of 60 minutes with a 6% volume fraction of TiO2 NPs, confirming a 22% enhancement in thermal conductivity. In this study, a pH of 8, a fourfold CMC, a constant temperature of 25ºC, and sonication for 10 minutes (see Figure 1) were used as control parameter conditions.…”
Section: Thermal Conductivity Of the Base Fluids And Tio2-water Nanofmentioning
confidence: 75%
See 1 more Smart Citation
“…This observation clearly indicated that the higher EG loading in the binary base fluids can give rise to lower thermal conductivity of base fluid and higher effective thermal conductivity ratio (k nf /k f ) in TiO 2 nanofluids. However, Sonawane et al [46] found that the relationship between the effective thermal conductivity ratio of TiO 2 nanofluids and that of base fluid was irregular. The thermal conductivity of 1 vol.% TiO 2 nanofluids followed the sequence: paraffin oil based nanofluid > water based nanofluid > EG based nanofluid, while that of pure base fluids followed the sequence: water > EG > paraffin oil.…”
Section: Influence Of Thermal Conductivity Of Base Fluidmentioning
confidence: 98%
“…Mansel et al [48] found two hours' sonication can increase the thermal conductivity of water based TiO 2 nanofluids due to the percolation effect in the aggregations. Sonawane et al [46] carried out a particular research on the effect of sonication time on the thermal conductivity of TiO 2 nanofluids. They found that for each of the three kinds of base fluids including water, EG and PO, the thermal conductivity of TiO 2 nanofluids increased first and then decreased as the sonication time increases.…”
Section: Influence Of Ultrasonic Vibrationmentioning
confidence: 99%